2021
DOI: 10.1116/6.0001006
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of the ladybird beetle adhesive foot fluid across various substrates

Abstract: Note: This paper is part of the Biointerphases Special Topic Collection on Biomimetics of Biointerfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, additional research is needed to verify the hypothesis that there is a direct correlation between the specialization of friction pads and body size [53]. Experimental evidence showing the non-Newtonian nature of adhesive fluid has only recently been confirmed [105]. Current tribological models revealed that both the interfacial interactions between the fluid and substrate as well as the chemistry of the bulk play an equally important role for establishing shear-thinning properties [105,291].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, additional research is needed to verify the hypothesis that there is a direct correlation between the specialization of friction pads and body size [53]. Experimental evidence showing the non-Newtonian nature of adhesive fluid has only recently been confirmed [105]. Current tribological models revealed that both the interfacial interactions between the fluid and substrate as well as the chemistry of the bulk play an equally important role for establishing shear-thinning properties [105,291].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence showing the non-Newtonian nature of adhesive fluid has only recently been confirmed [105]. Current tribological models revealed that both the interfacial interactions between the fluid and substrate as well as the chemistry of the bulk play an equally important role for establishing shear-thinning properties [105,291]. Therefore, further nano-tribological investigations are needed to gain additional insights into the origin of the observed friction forces of various insect species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation